Editorial: Redefining financial services - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Since the mid-1970s microfinance has become serious business. According to recent estimates, about 10,000 microfinance institutions (MFIs) are now providing small loans to 23 million people.